Relation early pregnancy between low birth weight incidence study at Palibelo Primary Health Center, Bima Regency: - - Daniati, Dana; Vegy Melati Sukma; Ade Elvina (Jurnal Kebidanan Besurek, 2025)
Low Birth Weight (LBW) is a health problem in society. Low Birth Weight (LBW) is defined as a baby born with a body weight of <2500 grams. Babies with low birth weight can cause inappropriate developmental disorders, both cognitively and motorically, compared to babies with normal birth weight. Babies with LBW also have a higher risk of death. The incidence of Low Birth Weight (LBW) babies in the world is more common in developing countries, contributing 96.5% (WHO, 2018). The aim of this research was to determine the relationship between early pregnancy and the incidence of low birth weight babies.This research was conducted at the Palibelo Community Health Center on December 11 2024, using an observational analytical research design with a cross sectional approach with the independent variable being early pregnancy and the dependent variable being the incidence of low birth weight babies. Data collection used secondary data obtained from medical records, the population was 185 respondents and the number of samples used was 127 respondents and data processing used univariate analysis, bivariate analysis with Chi Square test analysis. The distribution of data on maternal age showed that more mothers aged ≥ 20 years gave birth, 79.5%, and the distribution of data on the incidence of LBW showed that there were more babies with normal birth weight, 80.3%. Chi Square analysis shows that there is a relationship between early pregnancy and the incidence of LBW (p value = 0.000). Providing education to teenagers not to marry at an early age is very risky for reproductive health and the babies they will be born with so it can reduce cases of LBW.